"Textbook as a contradictory melting-pot": an analysis of multicultural content in Korean textbooks. Issue 1 (2nd January 2016) - Cho, Youngdal; Park, Yunkyoung
Abstract : In this study we will observe how multicultural content is covered in elementary and secondary schools in Korea. For this purpose, a total of 52 textbooks (social studies, ethics and Korean language from third to ninth grade) were analysed using two analysis frames. The first frame is the "multicultural content analysis frame (MCAF)" which analyses the structure and distribution of multicultural content in textbooks. It consists of three categories: (1) identity, (2) diversity and pluralism, and (3) social justice. The second frame is the "multicultural description analysis frame (MDAF)" which shows the perspectives from which the content is described. This frame consists of five categories: (1) balance of material distribution, (2) accuracy and scope of information, (3) distortion and stereotypes, (4) balance in perspectives, and (5) Korean-ethnic centredness. Since this multicultural content has contradictory structure and Korean-ethnicity centred perspectives, we propose several suggestions for restructuring textbooks from a multicultural education perspective and for the improvement of multicultural education in Korea.